Environmental management handbook. Volume 1, Managing global resources and universal processes - Fath, Brian D.; Jørgensen, Sven Erik, 1934- (Boca Raton : CRC Press, 2021)
"The Environmental Management Handbook is an excellent resource for finding basic knowledge on environmental systems. It reflects an extensive coverage of the field and includes the most important problems and solutions posed to environmental management today. In a very practical way, the handbook demonstrates the key processes and provisions for enhancing environmental management. The experience, evidence, methods, and models used in studying environmental management is presented here in six stand-alone volumes, arranged along the major environmental systems. The chapters are contributed by leading experts from around the globe"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental management -- Handbooks, manuals, etc; Environmental management